(3CSO GdZGHI aj eYQaI GdUMGHIs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ,J (B630 (3g` s
(3ChdgG (B:s
(3TGaY Hf GdTGjH Hf YHjO Hf YHO jRjO Hf gGTe Hf GdeWdH Hf YHO efGa s
(3BNQgG (B:s
(3hCHh fYje YHjOI HGdVe CjVkG gh GHf eGdc Hf geGe Hf eYhjI hbO PcQ fSHg ai eRjOI haO Ydi GdfHi Udi Gdg Ydjg hSde hGSde bGdg GHf GdMdHi fLR GdKGdK s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B228s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B346 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B13 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs